The Role of Google Classroom Accompanied by YouTube Media in Efforts to Improve The Quality of Microteaching Lectures in The Biology Department of IAIN Kerinci - Dewi Juita; Yusmaridi M (Universitas Riau, 2020)
This research is motivated by the unavailability of video recorder that serves to provide feedback on student performance in microteaching lectures. The purpose of this study was to obtain a description of student responses to the use of google classroom with youtube media in microteaching lectures and how the role of google classroom accompanied by youtube media in improving the quality of microteaching lectures. The researcher recorded the student’s performance, uploaded it to the youtube channel, and displayed it via google classroom. The method used is descriptive methods. The results showed that 94% of students agreed that the use of Google Classroom along with YouTube media could provide constructive feedback to students, 100% of students agreed with the use that could be an introspection material for students' teaching skills, and 90.6% of students agreed that through the use of it can improve the quality of microteaching lectures, which is characterized by an increase in students' teaching skills. The intended teaching skills are opening lessons, explaining material, questioning, giving reinforcement, making variation, using media, class management, and closing lessons. The improvement of the quality of microteaching lectures is in the medium category with <N-Gain> value of students by 0.54.